Digitalisasi Akuntansi, Persaingan dan Jejaring Sosial Pada UMKM Kuliner Palembang - Dwirini Dwirini; Shufia Zuhroh; Rini Subekti (Politeknik Ganesha Medan, 2025)
The phenomenon that is the subject of this research is the digitalization of accounting content which has been four years since the publication of the vision for Indonesia's payment system in 2025 which resulted in 5 (five) visions proposing a positive flow of digitalization developing in a conducive digital economic and financial ecosystem. This research aims to prove the influence of digitalization of accounting, competition, and social networks on modern management accounting in the MSME sector in the city of Palembang. From these problems, researchers see that there is digital potential for Palembang City MSMEs to be used as research objects, with 383 questionnaires to be processed. In analyzing data, researchers used SmartPLS. SmartPLS is an effective tool for analyzing complex relationship models with a large number of constructs and indicators. This research shows that the digitalization of accounting, competition and social networks have a significant positive influence. With the magnitude of the influence of each indicator in this research being R2 = 73.9%, this means that 73.9 percent of modern management accounting in the culinary sector of the city of Palembang is influenced by the third variable, namely digitalization of accounting, social networks and market competition and so on, 26.1 percent is influenced by variables outside this.